Breaking symmetry in device design for self-driven 2D material based photodetectors. Issue 15 (1st April 2020) - Wang, Qi; Zhou, Changjian; Chai, Yang
Abstract : By elaborating the concept of symmetry breaking in 2D material based photodetectors, we give a concise and generalized framework which covers existing photodetectors with self-driven properties. Abstract : The advent of graphene and other two-dimensional (2D) materials offers great potential for optoelectronic applications. Various device structures and novel mechanisms have been proposed to realize photodetectors with unique detecting properties. In this minireview, we focus on a self-driven photodetector that has great potential for low-power or even powerless operation required in the internet of things and wearable electronics. To address the general principle of self-driven properties, we propose and elaborate the concept of symmetry breaking in 2D material based self-driven photodetectors. We discuss various mechanisms of breaking symmetry for self-driven photodetectors, including asymmetrical contact engineering, field-induced asymmetry, PN homojunctions, and PN heterostructures. Typical device examples based on these mechanisms are reviewed and compared. The performance of current self-driven photodetectors is critically assessed and future directions are discussed towards the target application fields.